THE PROFESSIONAL RELIABILITY OF THE NATIONAL POLICE OF UKRAINE OFFICERS’: FIRST RESULTS OF EXPERIMENTAL WORK - Barko, Vadym; Vagina, Olena; Lunov, Vitalii; Chubata, Marina; Nastyuk, Andrii; Dei, Maryna; Bolshakova, Anastasiia (International Journal of Psychosocial Rehabilitation, 2020)
Based on the results of the expert assessment, the police officers were divided into three groups in terms of professional reliability, including the level of subjective professional experience, the development of professionally important qualities, work experience and personality characteristics. Materials and Methods. The SACS Questionnaire - "Strategic Approach to Coping Scale" (S. Hobfoll), Coping test by R. Lazarus, Multi-level personal questionnaire "Adaptivity", by A.H. Maklakov (1993), Life meaning orientations test The test of life meaning orientations is an adapted version of the test "Purpose in life" by J. Crumbaugh and L. Maholic, Questionnaire of the motivational structure of the personality by V. Milman, Questionnaire of the level of self-actualization by A. Maslow, The personal orientation questionnaire by V. Smekalo and H. Kucher. The 1 group (optimal level of professional reliability) included 54 police officers aged from 23 to 38 years old. The 2 group (sufficient level) included 57 people aged 24 to 37 years old. The length of service is from 2 to 8 years. The 3rd group (critical level) included 55 police officers aged 24 to 33 years old. The length of service is from 2 to 7 years. Based on the obtained results of experimental work, the program for developing the professional reliability of the administrative police officers is presented. The main tool for the implementation of the program is professionally psychological training - a comprehensive educational technology that allows you to realize the professional self-development and self-improvement of the policeman personality in the form of a continuous process. This training includes a system of methods, techniques and exercises that ensure the effective formation, development and correction of the main components of professional policeman reliability: axiological-semantic, motivational, cognitive, emotional-volitional and behavioral.